2011
DOI: 10.1007/s12052-011-0366-x
|View full text |Cite
|
Sign up to set email alerts
|

Freshman Undergraduate Biology Students’ Difficulties with the Concept of Common Ancestry

Abstract: All life on earth descended from a single common ancestor that existed several billion years ago; thus, any pair of organisms will have had a common ancestor at some point in their history. This concept is fundamental to an understanding of evolution and phylogeny. Developing an understanding of this concept is an important goal of evolution education and a part of most high school and college biology curricula. This study examines freshman undergraduate biology majors' understanding and application of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Recent studies of student responses to natural selection items found that students gave different responses depending on the context of the item (Nehm and Ha 2011;Nehm et al 2012;Nettle 2010;Opfer et al 2012;White and Yamamoto 2011). For example, undergraduate biology students said that organisms lost traits over time because they did not use them or that the organism shifted energy allocation to other more important processes, but did not use those ideas to respond to items about trait gain (Nehm and Ha 2011).…”
Section: The Relevance Of Item Context To Student Ideasmentioning
confidence: 99%
“…Recent studies of student responses to natural selection items found that students gave different responses depending on the context of the item (Nehm and Ha 2011;Nehm et al 2012;Nettle 2010;Opfer et al 2012;White and Yamamoto 2011). For example, undergraduate biology students said that organisms lost traits over time because they did not use them or that the organism shifted energy allocation to other more important processes, but did not use those ideas to respond to items about trait gain (Nehm and Ha 2011).…”
Section: The Relevance Of Item Context To Student Ideasmentioning
confidence: 99%
“…Other studies have found that freshman undergraduate biology students' understanding of common ancestry does not often include a common ancestor for all organisms (White and Yamamoto 2012).…”
Section: Structural Features Of a Phylogenetic Treementioning
confidence: 98%
“…Catley et al () demonstrated that students’ understanding of tree‐thinking and macroevolutionary concepts can be substantially increased by focused instruction, but noted that they still struggled with the concept of most recent common ancestry (MRCA), which they argue is not made explicit in biology textbooks but should be. Common ancestry was also found to be a difficult concept in a study for freshman undergraduate biology majors, who consistently saw common ancestry as a continuum from less to more probable rather than a binary yes/no trait, viewed taxonomic distance as the most significant factor in determining the likelihood of common ancestry, and thought that humans are less likely to be connected to common ancestors than nonhumans are (White and Yamamoto, ). A study that compared two semesters of an introductory biology class in which tree‐thinking was taught as an organizing framework for the course with one in which those concepts were taught as stand‐alone topics found significant increases in students’ ability to read trees in both semesters, but a significant increase in students’ acceptance of evolution only in the former semester—and that post‐test evolution acceptance was correlated with gains in tree‐thinking abilities (Gibson and Hoefnagels, ).…”
Section: Obstacles To Teaching and Learning Evolutionmentioning
confidence: 99%